Penerapan Permen PANRB 29/2022 dalam Penilaian Kinerja Pelayanan Publik di Kecamatan Rungkut Kota Surabaya - Rohmalia, Fitri; Vidya Imanuari Pertiwi (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Rungkut District is one of the public service units with the lowest community satisfaction index in Surabaya City District in 2023. So monitoring and evaluation needs to be carried out in order to get recommendations and improvements. The aim of this research is to assess the performance of public services based on the regulations of the Minister for Administrative Reform and Bureaucratic Reform (PermenPAN RB) Number 29 of 2022. The research method used is descriptive qualitative research with a content analysis approach. Data collection techniques through observation, documentation and assessment follow the format of PermenPAN RB 29/2022 with form-02 calculations as the evaluator. The results of the research show that the performance of public services in Rungkut District is good but with caveats. Because it can be seen from the service policy aspect that the availability of standard information and service announcements is an obligation of service providers; aspects of HR professionalism, namely service implementers who are responsive and implement a culture of service implementers; aspects of facilities and infrastructure, namely the availability of facilities and infrastructure supporting services; aspects of public service information systems to inform and support service operations so that they become known to the public; the complaint consultation aspect, namely the availability of a special place for consultation and complaints to provide information and complaints to the public; The existence of public service innovation makes it easier to provide online licensing services. Suggestions from researchers need to increase the media for publishing service information and providing infrastructure for disability groups.